PERGESERAN MAKNA RITUAL IBADAH DI ERA DIGITAL - Udji - Asiyah; Ratna Azis Prasetyo; Sudjak Sudjak (Universitas Negeri Malang, 2019)
The presence of Smartphones is the reason for the shifting of meaning in rituals of worship why today and first are different, places that should be sacred seem to be new tourist attractions, many people have selfies in front of them then uploaded in social media, scenes like this were not found in the past. The writing of this article aims to explain the shift in the meaning of worship rituals that should be enjoyed but shift to prioritizing busyness looking for a good perspective as a background for taking pictures or recording videos with no regard for the special worship and safety of other worshipers. This study was conducted qualitatively, data obtained through observation and interviews, the results of this study found that social piety is better able to eliminate the use of technological tools in worship than ritual piety which tends to explore technological equipment.